Impact of COVID-19 on viral respiratory infection epidemiology in young children: A single-center analysis - Shen, David Paul; Vermeulen, François; Debeer, Anne; Lagrou, Katrien; Smits, Anne (Frontiers in Public Health, 2022)
The COVID-19 pandemic impacts different health aspects. Concomitant with the adoption of nonpharmaceutical interventions (NPIs) to reduce the spread of SARS-CoV-2, global surveillance studies reported a reduction in occurrence of respiratory pathogens like influenza A and B virus (IAV & IBV) and respiratory syncytial virus (RSV). We hypothesized to observe this collateral benefit on viral respiratory infection epidemiology in young children. Respiratory samples of children aged below 6 years, presenting at the outpatient clinic, emergency department, or pediatric infectious diseases department of the University Hospitals Leuven, between April 2017 and April 2021 were retrospectively analyzed. The occurrence (positivity rate), and seasonal patterns of viral respiratory infections were described. Chi-squared or Fisher’s exact test (and Bonferroni correction) were used to explore differences in occurrence between 2020-2021 and previous 12-month (April to April) periods. We included 3020 samples (453 respiratory panels, 2567 single SARS-CoV-2 PCR tests). IAV and IBV were not detected from March and January 2020, respectively. For IAV, positivity rate in 2020-2021 (0%, n=0) was significantly different from 2018-2019 (12.4%, n=17) (p<0.001) and 2019-2020 (15.4%, n=19) (p<0.001). IBV positivity rate in 2020-2021 (0%, n=0) was not significantly different than previous periods. RSV occurrence was significantly lower in 2020-2021 (3.2%, n=3), compared to 2017-2018 (15.0%, n=15) (p=0.006), 2018-2019 (16.1%, n=22) (p=0.002) and 2019-2020 (22.8%, n=28) (p<0.001). The RSV (winter) peak was absent and presented later (March-April 2021). Positivity rate of parainfluenza virus 3 (PIV-3) was significantly higher in 2020-2021 (11.8%, n=11) than 2017-2018 (1%, n=1) (p=0.002). PIV-3 was absent from April 2020 to January 2021, whereas no clear seasonal pattern was distinguished the other years. For the other viruses tested, no significant differences in occurrence were observed between 2020-2021 and previous periods. From March 2020 onwards, 20 cases (0.7%) of SARS-CoV-2 were identified. These findings reinforce the hypothesis of NPIs impacting the epidemiology of influenza viruses and RSV in young children. Compared to previous periods, no IAV and IBV cases were observed in the 2020-2021 study period, and the RSV peak occurred later. Since the pandemic is still ongoing, continuation of epidemiological surveillance, even on a larger scale, is indicated.